Negative symptoms and their association with depressive symptoms in the long-term course of schizophrenia - Heiden, Wolfram an der; Leber, Anne; Häfner, Heinz (European archives of psychiatry and clinical neuroscience, 2016)
Depressive symptoms abound in schizophrenia and even in subclinical states of the disorder. We studied the frequency of these symptoms and their relationship to negative symptoms from the first psychotic episode on over a long-term course of 134 months on data for 107 patients in our ABC Schizophrenia Study. Prevalence rates of 90 % for presenting at least one negative symptom and of 60 % for presenting at least one depressive symptom in the first psychotic episode illustrate the frequency of these syndromes. After the remission of psychosis the rates fell to 50 % (negative symptoms) and 40 % (depressive symptoms) over a period of 5 years, remaining stable thereafter. After we broke the negative syndrome down into (SANS) subsyndromes, a positive association emerged between anhedonia and depressive symptoms and remained stable over the entire period studied. In contrast, the association between abulia and depression grew increasingly pronounced over the illness course. However, a more detailed look revealed this to be the case in female patients only, whereas male patients showed no such association of these symptom dimensions. We have no explanation at hand for this sex difference yet.